Dominant factors controlling glacial and interglacial variations in the treeline elevation in tropical Africa - Wu, Haibin; Guiot, Joël; Brewer, Simon; Guo, Zhengtang; Peng, Changhui (Proceedings of the National Academy of Sciences, 2007)
The knowledge of tropical palaeoclimates is crucial for understanding global climate change, because it is a test bench for general circulation models that are ultimately used to predict future global warming. A longstanding issue concerning the last glacial maximum in the tropics is the discrepancy between the decrease in sea-surface temperatures reconstructed from marine proxies and the high-elevation decrease in land temperatures estimated from indicators of treeline elevation. In this study, an improved inverse vegetation modeling approach is used to quantitatively reconstruct palaeoclimate and to estimate the effects of different factors (temperature, precipitation, and atmospheric CO 2 concentration) on changes in treeline elevation based on a set of pollen data covering an altitudinal range from 100 to 3,140 m above sea level in Africa. We show that lowering of the African treeline during the last glacial maximum was primarily triggered by regional drying, especially at upper elevations, and was amplified by decreases in atmospheric CO 2 concentration and perhaps temperature. This contrasts with scenarios for the Holocene and future climates, in which the increase in treeline elevation will be dominated by temperature. Our results suggest that previous temperature changes inferred from tropical treeline shifts may have been overestimated for low-CO 2 glacial periods, because the limiting factors that control changes in treeline elevation differ between glacial and interglacial periods.

Building a "Green" Railway in China - Peng, Changhui; Ouyang, Hua; Gao, Qiong; Jiang, Yuan; Zhang, Feng; Li, Jun; Yu, Qiang (Science, 2007)

A Simulation of Temporal and Spatial Variations in Carbon at Landscape Level: A Case Study for Lake Abitibi Model Forest in Ontario, Canada - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai; Chen, Jiaxin; Parton, Sue (Mitigation and Adaptation Strategies for Global Change, 2007)

On the effects of vertical air velocity on winter precipitation types - Thériault, J. M.; Stewart, R. E. (Natural Hazards and Earth System Sciences, 2007)
Abstract. The various precipitation types formed within winter storms (such as snow, wet snow and freezing rain) often lead to very hazardous weather conditions. These types of precipitation often occur during the passage of a warm front as a warm air mass ascends over a cold air mass. To address this issue further, we used a one-dimensional kinematic cloud model to simulate this gentle ascent (≤10 cm/s) of warm air. The initial temperature profile has an above 0°C inversion, a lower subfreezing layer, and precipitation falls from above the temperature inversion. The cloud model is coupled to a double-moment microphysics scheme that simulates the production of various types of winter precipitation. The results are compared with those from a previous study carried out in still air. Based on the temporal evolution of surface precipitation, snow reaches the surface significantly faster than in still air whereas other precipitation types including freezing rain and ice pellets have a shorter duration. Overall, even weak background vertical ascent has an important impact on the precipitation reaching the surface, the time of the elimination of the melting layer, and also the evolution of the lower subfreezing layer.

Growth and structure development of semi-natural larch-spruce-fir (Larix olgensis–Picea jezoensis–Abies nephrolepis) forests in northeast China: 12-year results after thinning - Lei, Xiangdong; Lu, Yuanchang; Peng, Changhui; Zhang, Xiaopeng; Chang, Jie; Hong, Lingxia (Forest Ecology and Management, 2007)

Meta-analysis and its application in global change research - Lei, XiangDong; Peng, ChangHui; Tian, DaLun; Sun, JianFeng (Chinese Science Bulletin, 2007)

Satellite-based estimation of biomass carbon stocks for northeast China's forests between 1982 and 1999 - Tan, Kun; Piao, Shilong; Peng, Changhui; Fang, Jingyun (Forest Ecology and Management, 2007)

Carbon storage by ecological service forests in Zhejiang Province, subtropical China - Zhang, Jun; Ge, Ying; Chang, Jie; Jiang, Bo; Jiang, Hong; Peng, Changhui; Zhu, Jinru; Yuan, Weigao; Qi, Lianzhong; Yu, Shuquan (Forest Ecology and Management, 2007)